Social Reality-Based Arabic Language Learning in Islamic Senior High School - Ahmad Nurcholis; Muhamad Asngad Rudisunhaji; Timbul Timbul; Heri Efendi; Siti Marpuah (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
Social reality is an interesting issue in Arabic learning in madrasas because students can connect the subject matter with the phenomenon in the community. The purpose of this study was to analyze the success of MA Sirojut Tholibin Bacem Sutojayan Blitar in implementing social reality-based Arabic learning. It is qualitative research with an exploratory approach and phenomenological analysis. This study used the theory of social reality initiated by Paul Ricoeur (in 1973). The principal of Paul Ricoeur said that human actions in social reality are symbols of language, while these symbols invite certain thoughts and interpretations. The results of this study indicated that MA Sirojut Tholibin had succeeded in implementing social reality-based Arabic learning. The students’ Arabic language competence is increasing through social reality approaches such as learning ethics, juvenile delinquency, and the influence of social media. The learning media used included news articles, newspapers, websites, and scientific articles.